Gasto público de la dirección agraria de Loreto y su relación con el gasto de la división funcional agraria nacional periodo 2020 – 2024 - Taza Perez, Alison Paola (2025)
The inefficiency and disorganization in the management of public spending in the agricultural sector, characterized by structural deficiencies and low budget execution, limits support for family farming, weakens the sector's competitiveness, and jeopardizes food security and sustainable rural development. Therefore, the following research identified the relationship between the public spending of the agrarian directorate of Loreto and the spending of the national agrarian functional division period 2020-2024, considering a quantitative approach of an observational type and a correlational non-experimental design, including as a study population the budget data corresponding to the study variables, the results showed that there is no statistically significant relationship between total regional and national spending, which reflects a weak intergovernmental articulation, likewise, a positive and significant relationship was identified between current expenses of both levels, which indicates operational coherence in the resources assigned to operation, in contrast, no significant relationship was found in capital spending, which suggests autonomous investment planning in Loreto, likewise, a growing trend was observed in regional public spending, especially in personnel, and a strong capital execution in 2024, at the national level, spending showed a structural reconfiguration, with greater rigidity in the personnel component, the descriptive analysis revealed a worrying drop in goods and services in Loreto, reducing the entity's operational capacity. Therefore, it is necessary to improve the coordinated planning and functional balance of public agricultural spending.